Analisis Deskriptif Rasio Perputaran Persediaan dan Rasio Perputaran Bahan Baku,dan Biaya Produksi PT Fast Food Indonesia Tbk (KFC) : Descriptive Analysis of Inventory Turnover Ratio and Raw Material Turnover Ratio, and Production Cost Ratio of PT Fast Food Indonesia Tbk Period 2022-2025 - I'anatunisa I'anatunisa; Rista Afyani; Siti Nur Kholisoh; Vinka Ramadhani; Supriyati Supriyati (PT Cakrawarti Empat Proksi, 2026)
Uncertainty in macroeconomic conditions, inflationary pressure on food commodity prices, and fierce competition in the fast food industry require companies to optimize their operational efficiency and logistics management strictly. This study aims to describe and analyze the development of the Inventory Turnover Ratio, Raw Material Turnover Ratio, and Production Cost Ratio and explain the logical relationship between these ratios in PT Fast Food Indonesia Tbk for the period of 2022 to 2025. The research method used is a descriptive quantitative method. The type of data used is secondary data in the form of quarterly financial statements of companies officially obtained from the Indonesia Stock Exchange (IDX) with a total sample of 12 time series observations. The analysis was carried out using descriptive statistics including the calculation of the average value (mean), maximum value, and minimum value in the financial ratio indicator. The results of the analysis show that during the observation period of 2022–2025, the Inventory Turnover Ratio and the Raw Material Turnover Ratio generally show dynamic logistics management performance, while the company's Production Cost Ratio absorbs a fairly significant proportion of total operating income on average. Quantitatively descriptive, the dynamics of Inventory Turnover and raw materials that tend to fluctuate descriptively show an inverse relationship pattern to fluctuations in the production cost ratio. The speed of activity ratio in managing logistics inventory and kitchen raw materials indicates a trend in the efficiency of production costs in real terms in KFC restaurants from year to year